TINJAUAN HUKUM INTERNASIONAL TERHADAP KASUS PENGGUNAAN SENJATA KIMIA OLEH SURIAH - Steffy Steffy; Jelly Leviza; Arif Arif (Journal of USU International Law, 2014)
ABSTRACTWar is something inevitable. Since war is something inevitable, people then made a regulation regulating war, which is currently known as International Humanitarian Law or IHL. This regulating war regulation is meant to make sure that a war is not done without a limit. One of the restrictions regulated by international humanitarian law is about weapons which are allowed by international humanitarian law. International humanitarian law prohibits the usage of mass destruction weapons in a war. One of the mass destruction weapons prohibited in a war is the chemical weapons. The problems which are going to be discussed in this research is first, how is international humanitarian law regarding the usage of chemical weapons in an armed conflict; second, what authority does United Nations have in cases where chemical weapons are used in an armed conflict based on international law; and third, how is international law regarding the usage of chemical weapons by Syria. The research method used in this research is the normative legal method which is done by collecting library materials and secondary data. Library materials and secondary data meant in this research is applicable international law which regulates the prohibition of the usage of chemical weapons as regulated in various international legal instruments. The result of this research is that the usage of chemical weapons by Syria has violated several international legal instruments, including Hague Conventions of 1899 and 1907, Geneva Protocol of 1925, UN Charter, Rome Statute of International Criminal Court 1998. The usage of chemical weapons by Syria has also violated international customs of war. Since international cannot be forced its enforcement, it is recommended that Syria is given a sanction, such as suspension of rights of Syria as part of General Assembly in UN. Keyword : Senjata Kimia, Suriah, Hukum Internasional